The Effect Of Management Information System Quality On The Risk-Based Capital (RBC) Solvency Ratio Through Operational Efficiency in Indonesian Insurance Companies - Rozak Hackiki (PT Naureen Digital Education, 2026)
Indonesia's insurance industry is facing increasingly stringent regulatory pressures, especially related to the fulfillment of the Risk-Based Capital (RBC) solvency ratio set by the Financial Services Authority at a minimum of 120%. This study aims to analyze the influence of the quality of Management Information System on the RBC ratio through operational efficiency as a mediating variable in insurance companies in Indonesia. The method used is a Systematic Literature Review of 30 selected scientific journals sourced from high-reputable databases. The results of the study show that the quality of SIM has a positive and significant effect on operational efficiency through process optimization, data accuracy, and acceleration of managerial decision-making. Operational efficiency was further proven to have a positive effect on the RBC ratio through the mechanism of capital surplus accumulation resulting from the reduction of the burden of unproductive costs. Simultaneously, operational efficiency has been shown to mediate the relationship between SIM quality and RBC ratio significantly. These findings imply that strengthening the quality of information technology is a strategic prudential instrument that indirectly strengthens the long-term capital resilience and solvency of Indonesian insurance companies.